Pengaruh Price Earning Ratio, Current Ratio dan Return on Equity Terhadap Harga Saham Perusahaan Minyak dan Gas Bumi yang Terdaftar di Bursa Efek Indonesia Periode 2016-2022 - Debby Marsella (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the simultaneous and partial influence of the Price Earning Ratio, Current Ratio and Return on Equity variables on the share prices of oil and gas companies listed on the Indonesia Stock Exchange for the 2016-2022 period. The variables Price Earning Ratio, Current Ratio and Return on Equity are independent variables in this research and Stock Price is the dependent variable in this research. The sampling technique used in this research was purposive sampling, so 4 companies were obtained as research samples. The data used is secondary data in the form of financial reports, taken via www.idx.co.id and share prices taken from finance.yahoo.com. This research uses analytical methods and quantitative data with multiple linear regression analysis modeling. The conclusion of this research shows that the variables PER, CR and ROE simultaneously have a significant effect on stock prices according to the results of the F test with a sig value = 0.000 < 0.05. Partially, the PER variable has no significant effect on stock prices with a sig value of 0.817 > 0.05. The CR variable has a significant effect on stock prices with a sig value = 0.000 < 0.05. The ROE variable has no significant effect on share prices with a sig value of 0.271 > 0.05.